2015
DOI: 10.1027/0227-5910/a000330
|View full text |Cite
|
Sign up to set email alerts
|

Using the Theory of Planned Behavior to Predict College Students’ Intention to Intervene With a Suicidal Individual

Abstract: Theory of planned behavior is an effective framework for understanding peers' intention to intervene with a suicidal individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…The number of suicide risk assessment training hours received (regardless of whether core competencies were addressed) was correlated with the number of suicide risk assessments conducted as well as perceived behavioral control. This finding is consistent with previous studies of mental health professionals and reported self-efficacy in being able to conduct suicide prevention behaviors (Aldrich, 2015;Aseltine et al, 2007;Bean & Baber, 2011). However, perceived behavioral control was also found to be related to the participants' year in the doctoral program.…”
Section: Discussionsupporting
confidence: 93%
“…The number of suicide risk assessment training hours received (regardless of whether core competencies were addressed) was correlated with the number of suicide risk assessments conducted as well as perceived behavioral control. This finding is consistent with previous studies of mental health professionals and reported self-efficacy in being able to conduct suicide prevention behaviors (Aldrich, 2015;Aseltine et al, 2007;Bean & Baber, 2011). However, perceived behavioral control was also found to be related to the participants' year in the doctoral program.…”
Section: Discussionsupporting
confidence: 93%
“…The Willingness to Intervene against Suicide questionnaire (WIS; Aldrich et al, 2014) was developed based on the TBP (Ajzen, 1985) and is composed of four subscales measuring attitudes, subjective norms, PBC and intention to intervene. Previous research shows the subscales within the WIS range in reliability from .72 to .90 (Aldrich, 2015; Aldrich et al, 2014). Both the pretest and posttest used the WIS subscales to measure attitudes about suicide intervention (14 items, pretest, α = .83; posttest, α = .75), subjective norms regarding support from important others (9 items, pretest, α = .77; posttest, α = .75), PBC regarding intervention (17 items, pretest, α = .87; posttest, α = .91), intention to intervene with a suicidal individual (20 items, pretest, α = .89; posttest, α = .88) and experience with mental health issues, family history of mental health issues, experience with suicide, experience with intervention and demographic information.…”
Section: Methodsmentioning
confidence: 99%
“…This was higher than both adults aged 26–49 (1.3%) and adults aged 50 or older (0.5%) (SAMSHA, 2017). Aldrich (2015) collected data from 367 undergraduate college students and found that 1.4% reported they had personally attempted suicide. This is consistent with findings from other research (ACHC, 2016; SAMSHA, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…were measured through a designed and validated questionnaire by Rezapur-Shahkolai et al [ 3 ], Aldrich [ 27 ], George [ 28 ], and Matheson [ 29 ]. The questionnaire included 25 three-choice questions evaluating knowledge.…”
Section: Methodsmentioning
confidence: 99%